The Implementatyion Off Problem Based Learning Model (PBL) on Teachers and Students Grade Five Elementary Schools in Surakarta City - N, Issufiah Dwi; Sunardi, Sunardi; W, Sri Anitah; Gunarhadi, Gunarhadi (International Journal of Active Learning, 2018)
The role of teachers is very important in the learning process to create a quality learning atmosphere so as to produce a quality output as well. The fact that there are still many obstacles in the field related to the role of a competent and professional teachers. There are still many students who have not been able to optimally apply the results of education in school into real life. This is what needs to get attention, that teachers as the spearhead of the success of national education goals that can be achieved by students. This study aims to find out how the form of planning and implementation of learning in elementary schools in applying the model of PBL, and how students' achievements in solving problems. Research with descriptive method, collecting data through questionnaire, test, and interview. Data analysis is statistically descriptive with calculation of percentage and graph. The results showed that the planning and implementation of learning with Problem Base Learning (PBL) is still low on average. The lowest score of teacher questionnaire results is on implementing scientific learning as much as 29.7% and understanding of new scientific steps 30%. Student learning outcomes measured through tests with three categories indicate the percentage of students in completing the lowest test is in the problem-solving